Two new species of Parastenocarididae (Copepoda, Harpacticoida) from India - Reddy, Yenumula Ranga; Totakura, Venkateswara Rao; Shaik, Shabuddin (Zootaxa, 2016)
To date, 20 species of Parastenocarididae are known from the Indian subcontinent. This paper gives the description of two more new species from the coastal deltaic belt of the Rivers Krishna and Godavari in the Andhra Pradesh state of the southeastern Indian peninsula. They are: Parastenocaris enckelli n. sp. from a hyporheic habitat, and Dussartstenocaris bisetosa n. sp. from a farm bore. Parastenocaris enckelli belongs to the brevipes-group of the genus Parastenocaris Kessler, 1913 sensu Lang 1948 and Reid 1995, and is characterized by the following features: the male leg 4 basal complex consists of a large chitinized plate, with two digitiform hyaline structures at its proximal outer corner of the anterior surface, and one smooth, moderately strong, claw-like spine at the inner distal corner of basis; the endopod of the same leg is membranous, with bulbous proximal part having a diagonal row of three spinules, and its distal part is drawn out into smooth pointed structure; and the male leg 3 ancestral proximal segment is subproximally dilated, elongate, with ladle-shaped apophysis, which is slightly longer than the spiniform thumb. Parastenocaris enckelli is closely related to the Indian P. edakkal Totakura, Ranga Reddy & Shaik, 2014, and the Sri Lankan P. brincki Enckell, 1970. To accommodate Dussartstenocaris bisetosa in the monotypic Western Australian genus Dussartstenocaris Karanovic & Cooper, 2011, three of the original generic criteria are amended. D. bisetosa is chiefly characterized by the complex exopodal thumb on the male leg 3, the caudal ramus having only two lateral setae located slightly anterior to its midlength together with the distally inserted dorsal seta, and also the presence of a short spiniform process at the inner distal corner of leg 5 in both sexes. Dussartstenocaris bisetosa differs from D. idioxenos Karanovic & Cooper, 2011, by its shorter caudal rami, distinctly ornamented anal somite, two long modified spinules on the male leg 4 coxa, and rather small fifth legs with only two setae each in both sexes and smooth inner margins. This is the first report of the genus Dussartstenocaris from the Indian subcontinent. Brief biogeographic notes are also given for the two new species.